Formulasi Tablet Effervescent Ekstrak Daun Kelor (Moringa oleifera L.) sebagai Pemenuhan Nutrisi untuk Pencegahan Stunting - Elpa Giovana Zola; Eka Syafitri; Rahmadevi Rahmadevi; Dea Ayu Agustina (Journal of Pharmaceutical and Sciences, 2026)
Stunting remains a significant nutritional problem in Indonesia, requiring practical and acceptable nutritional interventions. Moringa oleifera L. leaves are known to contain essential minerals such as zinc, iron, and iodine, which play an important role in supporting optimal growth. This study aimed to formulate effervescent tablets of Moringa leaf extract and evaluate their physical quality as an alternative nutritional supplement for stunting prevention. Moringa leaf extract was obtained through maceration and formulated into four effervescent tablet formulas with varying extract concentrations. The evaluations included granule flow properties, angle of repose, pH, size uniformity, weight uniformity, dispersion time, FTIR analysis, and hedonic testing. The results showed that all formulas met the physical quality requirements of effervescent tablets. The granules exhibited good flow characteristics with an angle of repose below 40°, while the tablet pH values ranged from 4,4 -5,8, indicating suitability for oral administration. All formulas complied with the standards for size and weight uniformity, and the dispersion time ranged from 1 to 2 minutes. FTIR analysis confirmed the presence of hydroxyl, carbonyl, nitroso, and benzene functional groups associated with flavonoids, saponins, and tannins, which contribute beneficial mineral content. Based on physical and organoleptic evaluations, Formula 2 showed the best combination of extract content and granule flow properties, while Formula 1 was the most preferred in terms of taste.